Patogenisitas Streptokokus Grup B pada Mencit Neonatus - HayatiO, Zinatul; Fadrial Karmil, Teuku (Jurnal Veteriner; Vol 10 No 4 (2009))
Group B Streptococci (GBS) are the major cause of serious infections in neonates, including pneumonia, septicemia and meningitis. Considering that GBS bacteria founded in Indonesia in our previous study is dissimilar as what have been found in foreign country particularly in its serotype distribution, therefore this research is extremely essential to be conducted in Indonesia in order to searching the vaccine candidate to be used in Indonesia. This research focused in pathogenicity test of each GBS isolates on animal model. Pathogenicity experiment has been done by early onset septicemia model approach to neonatal mouse. Pathogenicity test result that SR-7 isolates can cause the death of neonatal mouse 100% in early-onset infection. Whereas, SV-2 isolates cannot cause the neonatal mouse neither in early-onset nor in late-onset. From the serotype determination result at previous research found that SR-7 isolates is serotype isolates VI whilst SV-2 isolates is serotype III. This result has shown that SR-7 (serotype VI) isolates is the most pathogen and the SV-2 isolates is less pathogen.
Keywords: Grup B Streptococci, septicemia, meningitis, miceonatus